The analysis of the effect of piston speed on the operation of a refrigeration compressor operating in the area of wet steam - D. Kh. Sadvakasov; G. I. Chernov; V. S. Evdokimov; N. A. Raykovskiy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents a theoretical assessment of the effect of the piston speed on the energy efficiency of a steam compression refrigeration cycle based on compression in the area of wet steam, implemented in a low-speed refrigeration compressor stage. The refrigerant R134a was chosen as the working fluid. The numerical calculation of the working process of a refrigeration compressor operating in the field of wet steam was carried out on the basis of a mathematical model and implemented using the Runge– Kutta method of the 4th order in the MathCad package. The calculation of heat transfer was carried out according to the generalized formula for film boiling — condensation inside the pipes. Based on the calculation, the analysis of the effect of the piston speed on the characteristics of the compressor workflow, in particular, on the appearance of its indicator diagram, was carried out.